Ecopreneurship Pesantren Inovasi Pengolahan Sabut Kelapa Menjadi Green Product Cocopeat - Fahimah, Mar'atul; Rahmatika, Arivatu Ni’mati; Rahmawati, Ita (STMIK Royal, 2024)
Coconut fiber or coir is the outer part of the coconut fruit that is often considered as waste after the meat and water are extracted. Without proper processing, discarded coconut fibers will accumulate in the surrounding environment and creating a number of environmental problems. This community service activity aims to increase the knowledge and skills of the students through training in processing coconut fiber waste into cocopeat using a chopping machine. This cocopeat product can be used as an organic planting medium. This training was held at the Al Mimbar boarding school in Jombang, East Java, which can create an alternative source of income for the boarding school and foster environmental awareness among students. The methods used in this training include socialization and hands-on practice in making cocopeat. The results of this activity show that the students are increasingly aware of the environment, are able to process coconut fiber waste into quality cocopeat, and understand the economic value of the product as well as the market potential that can be utilized by the pesantren to get additional sources of funding from the sales of cocopeat. Thus, this program can be the first step for pesantren in developing sustainable environment-based businesses, as well as making a positive contribution to improving the local economy.Keywords: ecopreneurship; coconut fiber; cocopeat Abstrak: Serabut kelapa atau sabut kelapa adalah bagian luar dari buah kelapa yang sering dianggap sebagai limbah setelah diambil daging dan airnya. Tanpa pengolahan yang tepat, serabut kelapa dibuang akan menumpuk di lingkungan sekitar sehingga menciptakan sejumlah masalah lingkungan. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan para santri melalui pelatihan pengolahan limbah serabut kelapa menjadi cocopeat dengan menggunakan mesin pencacah. Produk cocopeat ini dapat digunakan sebagai media tanam organik. Pelatihan ini diselenggarakan di pondok pesantren Al Mimbar Jombang Jawa Timur yang dapat menciptakan sumber pendapatan alternatif bagi pesantren dan menumbuhkan kesadaran lingkungan di kalangan santri. Metode yang digunakan dalam pelatihan ini meliputi sosialisasi dan praktek langsung pembuatan cocopeat. Hasil dari kegiatan ini menunjukkan bahwa para santri semakin sadar akan lingkungan, mampu mengolah limbah serabut kelapa menjadi cocopeat berkualitas, dan memahami nilai ekonomis dari produk tersebut serta potensi pasar yang dapat dimanfaatkan pesantren mendapatkan tambahan sumber pendanaan dari pendapat penjualan cocopeat. Dengan demikian, program ini dapat menjadi langkah awal bagi pesantren dalam mengembangkan usaha berbasis lingkungan yang berkelanjutan, serta memberikan kontribusi positif bagi peningkatan perekonomian lokal.Kata kunci: ecoprenuership; sabut kelapa; cocopeat